A fatherless child autobiographical perspectives on African American men - Green, Tara T. (University of Missouri Press, 2009)
"Examining the works of Langston Hughes, Richard Wright, Malcolm X, and Barack Obama, Green portrays the intersecting experiences of generations of black men during the twentieth century both before and after the civil rights movement, revealing the impact of fatherlessness on racial and gender identity formation"--Provided by publisher.